Ethnicity, Gender and Social Change - Bradley, Harriet. author. aut Link
X, 249 p.
Keywords: Ethnicity, Gender and Social Change explores the social space occupied by both gender and ethnicity. As recognition of the sociological importance of gender and ethnicity has grown, so has the opportunity for exploring the intersections between them. This volume brings together both theoretical reflections and new research in this key area. For the sociologist this presents a conceptual challenge, while for the individual it may present a series of dilemmas. These are intriguingly traced out in studies which take us from Punjabi families in the UK, to Surinamese migrants in Amsterdam, to Hindu and Muslim women and Black nurses in Britain, the African and Asian diasporas, and gender identity in post-Soviet Latvia.